Lifestyle and dietary factors in relation to prostate cancer risk. (3rd October 2015) - Alvarez-Cubero, Maria Jesus; Pascual-Geler, Manrique; Rivas, Ana; Martinez-Gonzalez, Luis Javier; Saiz, Maria; Lorente, Jose Antonio; Cozar, Jose Manuel
Abstract: The aim of the present study was to determine the association between the socio-demographic, lifestyle factors, and dietary habits with the risk of prostate cancer (PC) in a case–control study of Spanish men. None of the socio-demographic, lifestyle or dietetic variables was found predictors of PC risk. Body mass index was associated with an increased risk for aggressive PC and fruit consumption with lower Gleason scores, thus less aggressive cancers. Nonetheless, after applying Bonferroni correction, these variables were not still associated with PC aggressiveness. More adequately, powered epidemiological studies that measure the effect of lifestyle and dietary intake in PC risk and aggressiveness are warranted to further elucidate the role of these modifiable factors on PC etiology.